Safeguarding of Malaysian folktale through adventure game for teenager. - Harun, Harryizman; Alwi, Asmidah; Othman, Azliza; Annamalai, Subashini (2019)
The folktale is part of people's culture and heritage which represents the identity of a society. Malaysia is prosperous with folktale which is traditionally diffused verbally from generation to generation. Inopportunely, this heritage is slowly being forgotten by the younger generations especially the teenagers. The study aims to safeguard the local folktale through adventure game for the teenagers. In the context of the study, Bawang Putih Bawang Merah was selected. In order to thrust the study toward achieving the aim stated, the study imposes four questions to be answered. The study seeks to discover the adventure game’s elements from the game guideline and user (teenager). Once found, it is a question of how both the elements can be employed to design and develop the folktale adventure game branded as Orkid Emas in the study. Based on the definitive version of the game, it is a question of obtaining the teenagers’ feedback about the game’s design and development and the safeguarding aspects. The methods employed in the study are the formal and semi-structured interview, document analysis, flowboarding and prototyping. As the results of the study, both the elements of an adventure game from the guidelines and users were ascertained. The Orkid Emas adventure game was successfully designed and developed using the combination of the elements. At large, positive feedbacks were obtained from the select representing teenagers regarding the Orkid Emas’ design and development, and folktale safeguarding aspects.